1989
DOI: 10.3164/jcbn.7.143
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and other determinants of iron and folate status in female adolescents.

Abstract: The relationships of diet, development, and maturation indices to the status of blood iron and folate indicators were studied among 233 adolescent girls aged 10-16 years. Statistically significant associations between total iron intake and hemoglobin, plasma iron,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Meat is the main source of well-absorbed iron, and it enhances the absorption of non-heme iron. In our study, as in the work of Bairati et al (1989) and Preziosi et al (1994), ascorbic acid intake, which is experimentally considered as a powerful enhancer of iron absorption, was not associated with any of the biological iron status indicators. Previous studies revealed that vitamin C was positively related to serum ferritin (Kenney, 1985;Hercberg et al, 1987).…”
Section: Discussionsupporting
confidence: 68%
“…Meat is the main source of well-absorbed iron, and it enhances the absorption of non-heme iron. In our study, as in the work of Bairati et al (1989) and Preziosi et al (1994), ascorbic acid intake, which is experimentally considered as a powerful enhancer of iron absorption, was not associated with any of the biological iron status indicators. Previous studies revealed that vitamin C was positively related to serum ferritin (Kenney, 1985;Hercberg et al, 1987).…”
Section: Discussionsupporting
confidence: 68%
“…Meat is the main source of well-absorbed iron and it enhances absorption of nonheme iron. In our study, as in the work of Bairati et al [34], ascorbic acid intake, which is experi mentally considered as a powerful enhancer of iron absorption, was not associated with any of the biological iron status indicators.…”
Section: Discussionsupporting
confidence: 63%
“…Most of the earlier studies used surrogate estimates of menstrual blood loss such as self-reported duration (Razagui et al 1991), frequency of menstruation (Worthington-Roberts et al 1988) or pre-or postmenopausal status (i.e. menstrual blood loss or no menstrual blood loss; Kenney, 1985;Bairati et al 1989;Yokoi et al 1994). The results are inconsistent: one study found no association between self-reported estimated blood loss and serum ferritin level (Bairati et al 1989), whereas another found a positive correlation (Kenney, 1985).…”
Section: Discussionmentioning
confidence: 99%